DIFFERENCES IN THE QUALITY OF NUTRITION AND EATING HABITS BETWEEN 11 TO 13 YEAR OLD CHILDREN WHO PRACTICE MARTIAL ARTS AND NON-ATHLETE CHILDREN - Nermin Salkanović,; Džemal Huremović, (Sport Scientific And Practical Aspects, 2025)
The survey was conducted on a sample of 351 respondents, 11 to 13 year old male students from urban areas of the Zenica-Doboj Canton, 276 non-athletes, and 75 athletes who practice martial arts. The research problem was to determine the differences in nutritional habits and nutritional quality as well as body composition in 11 to 13 year old boys, who are practicing martial arts and boys who are not involved in sports. A sample of variables for assessing the quality of nutrition and eating habits was based on a questionnaire on the nutritional habits of the Cantonal Public Health Institute in Zenica-Doboj Canton. This questionnaire contains 31 questions, of which 29 questions relate to the quality of nutrition and eating habits, and 2 questions relate to the personal opinion on healthy nutrition and the frequency of physical activity. Analysis of the Mann Whitney test results, lead to a conclusion that a statistically significant difference in the nutritional quality and nutritional habits between these two groups of subjects exists.